Revealing the Investment Interests of Part-Time Working Students: Implications for Financial Literacy and Behavior - Koesoemasari, Dian Safitri Pantja; Surveyandini, Mayla; Putri, Juvita Ananda; Janah, Anisa Aulia (JASF: Journal of Accounting and Strategic Finance, 2023)
This study aims to explore the factors affecting the investment interest of part-time students at the Faculty of Economics and Business, Wijayakusuma University, Purwokerto. A total of 177 respondents were selected using the snowball sampling technique, and the data were analyzed through multiple linear regression with the step-wise method, utilizing Jamovi software. The findings indicate that both financial literacy and financial behavior have a significant positive impact on investment interest, with a significance level of 1%. In contrast, the income variable does not show a significant effect on investment interest. Three regression models were evaluated, all of which demonstrated a strong goodness of fit. The model with the best explanatory power reveals that students' investment interest is primarily influenced by their financial literacy and behavior, rather than their income. These results highlight the need for enhancing financial literacy and behavior through formal education and training programs, in order to boost investment interest among students.